2018
DOI: 10.1016/j.socscimed.2018.07.016
|View full text |Cite
|
Sign up to set email alerts
|

How and why studies disagree about the effects of education on health: A systematic review and meta-analysis of studies of compulsory schooling laws

Abstract: Rich literatures across multiple disciplines document the association between increased educational attainment and improved health. While quasi-experimental studies have exploited variation in educational policies to more rigorously estimate the health effects of education, there remains disagreement about whether education and health are causally linked. The aim of this study was to conduct a systematic review and meta-analysis to characterize this literature, with a focus on quasi-experimental studies of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 97 publications
4
97
1
1
Order By: Relevance
“…An extensive literature in economics and public health has used these reforms to examine the causal effect of schooling duration on a range of adult specific diseases and risk factors (Banks & Mazzona, 2012;Davies, Dickson, Davey Smith, van den Berg, & Windmeijer, 2018;Dursun & Cesur, 2016;Glymour, Kawachi, Jencks, & Berkman, 2008;Huang, 2015;Nafilyan, Avendano, & De Coulon, 2017;Nguyen et al, 2016;Schneeweis, Skirbekk, & Winter-Ebmer, 2014), health behaviors (Jurges, Reinhold, & Salm, 2011;Silles, 2015), health-related knowledge (Johnston, Lordan, Shields, & Suziedelyte, 2015), and mortality (Albouy & Lequien, 2009;Clark & Royer, 2013;Gathmann, Jurges, & Reinhold, 2015;Lager & Torssander, 2012;Lleras-Muney, 2005). However, a recent review and metaanalysis of the health effects of compulsory schooling laws identified a paucity of research on biomarkers of health (Hamad, Elser, Tran, Rehkopf, & Goodman, 2018). Indeed, only three studies to date have focused on biomarkers; and their findings offer contradictory evidence of a causal relationship.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive literature in economics and public health has used these reforms to examine the causal effect of schooling duration on a range of adult specific diseases and risk factors (Banks & Mazzona, 2012;Davies, Dickson, Davey Smith, van den Berg, & Windmeijer, 2018;Dursun & Cesur, 2016;Glymour, Kawachi, Jencks, & Berkman, 2008;Huang, 2015;Nafilyan, Avendano, & De Coulon, 2017;Nguyen et al, 2016;Schneeweis, Skirbekk, & Winter-Ebmer, 2014), health behaviors (Jurges, Reinhold, & Salm, 2011;Silles, 2015), health-related knowledge (Johnston, Lordan, Shields, & Suziedelyte, 2015), and mortality (Albouy & Lequien, 2009;Clark & Royer, 2013;Gathmann, Jurges, & Reinhold, 2015;Lager & Torssander, 2012;Lleras-Muney, 2005). However, a recent review and metaanalysis of the health effects of compulsory schooling laws identified a paucity of research on biomarkers of health (Hamad, Elser, Tran, Rehkopf, & Goodman, 2018). Indeed, only three studies to date have focused on biomarkers; and their findings offer contradictory evidence of a causal relationship.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…reform on 16 biological indicators of sub-clinical disease including anthropometrics, blood glucose, lipids, blood pressure, as well as liver and kidney function. This large array of biomarkers enables us to consider different health dimensions, as previous research has showed that compulsory schooling laws can improve some outcomes while negatively affecting others (Hamad et al, 2018). We use data from a unique population-based survey that collected both educational attainment data and extensive health and biological measures in nearly 60,000 adults living in France at the time of the study.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The major limitations in these studies is the difficulty of ruling out the confounding influence of individual characteristics such as intelligence or childhood socioeconomic status that may influence both schooling and late-life cognition. Evidence from studies in settings with very different confounders [5], or based on natural experiments that could not plausibly be influenced by individual characteristics [6], strengthens the overall evidence base, even if the new studies have different limitations.…”
mentioning
confidence: 80%
“…This tendency to publish only positive findings might explain why the extant quasi‐experimental literature shows that social policies produce a greater health benefit than we found in our review. For example, Hamad and colleague's meta‐analysis of quasi‐experimental evaluations of law‐mandated increases in schooling duration found that these policies were associated with decreased probability of obesity (effect size: −0.20; 95% CI −0.40 to −0.02) 112 . In our review, which included different interventions than those evaluated by Hamad and coauthors, experiments in the early life and education domain were not associated with lower obesity risk 49,52 …”
Section: Discussionmentioning
confidence: 99%